On Membership in the Reformed Church of Hungary - Szathmáry, Béla (Booklets of Sárospatak, 2025)
The Reformed Church of Hungary distinguishes between theological membership based on the confession of faith and membership defined by church law. This paper analyses the issues of church membership. It distinguishes between membership based on baptism in the Reformed Church, membership of a person baptised in another Christian church and membership based on church policy considerations. It briefly analyses the rules on the termination of membership. The author describes the gaps and inconsistencies in the legislation. The author suggests ways and means of correcting the shortcomings and eliminating the inconsistencies.
Keywords: reformed church membership; the origin of church membership; termination of church membership; Church policy